In or Out: Boundaries of Institutional and Noninstitutional Theatre Scene in Croatian Theatre - Kačić Rogošić, Višnja (Poznańskie Studia Slawistyczne, 2025)
The paper presents the boundaries between the contemporary Croatian institutional and non-institutional scene, focusing on terminology, history, performance spaces and aesthetic demarcations. It provides the analysis of the concepts of institutional, non-institutional, alternative, experimental and independent theatre as well as the time limits of the two areas and the problems in their determination. The history of institutional theatre is often linked to the idea of national theatre since the middle of the 19th century, while the independent theatre has been traced since the beginning of the 20th century. The article explores the influence of performance spaces on the aesthetic development of individual scenes. It concludes with an insight into the aesthetic boundaries of both scenes, which are becoming more and more blurred in the new social, political, cultural and financial circumstances.